5PSQ-125 The identification of health consequences associated with counterfeit medicine and illegal health product application using pharmacovigilance data. (23rd March 2022) - Vida, RG; Pozsgai, K; Vajda, P; Botz, L
Abstract : Background and importance: Information on the health damage caused by counterfeit medicines and healthcare products is not, or is only rarely found, in the scientific literature. As a result it is difficult to determine or describe in clinical practice the extent and probability of drug-related problems originating from these products and how to identify these harms in a hospital setting. Aim and objectives: Our aim was to assess the active pharmaceutical ingredients affected, the extent and characteristics of health consequences related to counterfeit medications based on the accessible product alerts and pharmacovigilance data. Material and methods: In addition to doing a literature search, we reviewed the World Health Organization (WHO) Medical Products Alert publications in the last 20 years and collected adverse drug reactions indicating a counterfeit medicine in the WHO VigiAccess database. Furthermore, we analysed the counterfeit medicine-related adverse drug reactions in the US Food and Drug Administration (FDA) Adverse Events Reporting System (FAERS) database. Results: The top 12 most commonly involved active substances internationally were alprazolam, amoxicillin/clavulanic acid, bevacizumab, diazepam, phenobarbital, flunitrazepam, glibenclamide, heparin, insulin, levonorgestrel, sildenafil and tadalafil. Between 2003 and 2020 in the FAERS database, we identified 3868 falsified drug-related adverse drug reactions, and in the last 5 years an average of 300–500 cases, which represents 0.018% of all reported adverse drug reactions. Based on the FAERS cases we have identified less predictable adverse drug reactions as well, with PDE-5 inhibitors causing vision loss and eye bleeding, and alprazolam causing foaming mouth and suicide attempt. Conclusion and relevance: Our study showed that pharmacovigilance and toxicovigilance data are suitable for the identification and detection of health damage caused by counterfeit drugs. With the national adaptation and the development of a specific prospective data collection methodology in the clinical setting, it may also be possible to identify cases in Hungary, which will be a great step towards the prevention of patients' health damage and death related to these products. We believe that clinical pharmacists should play a more definite role in adverse drug reaction identification and toxicovigilance. References and/or acknowledgements: Conflict of interest: No conflict of interest